Cognitive-Code Learning Theory and Foreign Language Learning Relations - Mehmet Demirezen (Informascope, 2014)
There are many competing theories on foreign language teaching. Teachers who have been trained in foreign-language education, bilingual education, ESL education, and related fields - such as linguistics - usually have learned about predominant second-language-learning theories and their correlated instructional implications (Fitzgerald, 1994:339). Cognitive -code learning theory (CCLT) is a theory of L1 and L2 studies and research. This view was developed in the 1960s as an alternative to Behaviorism (Richards & ‎S. Rodgers (2014:26).  CCLT is said to have briefly replaced behaviorism in the late 1960s.  At this time, Chomsky's theory of Transformational generative Grammar, which claimed language is rule-governed and creative, strongly emphasized rule-governed nature of language and language acquisition, rather than habit formation: this trend gave rise to CCLT in which language learners are encouraged to work out grammar rules deductively for themselves. According to Dulay et al. (1982:140), Chomsky and his followers, with their influential papers, influenced the theory of language, and also the theory of language learning 'overnight.'  Chomsky alone started to bombard the background of the Behaviorist Approach by his establishment of a new approach called the Cognitive-code Approach, which, in turn, gave an offspring called Cognitive code-learning Theory within the influences of Cognitive Psychology. It was intended as an alternative to the Audio-lingual Method which stresses habit formation as a learn-by-doing-activity (Demirezen, 1988a:161) within the process of language learning; also, it is contrary to Behavioral perspective, the Developmental perspective and the Constructivist perspective. Because of emphasis of Cognitive Theory, which the initiator of CCLT, on studying a foreign language as a system of rules and rule-governed behaviors and knowledge, the cognitive approach is sometimes considered the modern version of the grammar-translation method. CCLT is a subset of Cognitive- code Approach (Richards & ‎Rodgers (2014). It was also advocated by cognitive psychologists and applied linguists such as J. B. Carroll (1916-2003) and K. Chastain (1971), in the 1960s.  J. B. Carroll was an American psychologist known for his contributions to psychology and educational linguistics.  CCLT is also based on Gestalt psychology which states learning should be holistic. Carroll and Chastain proposed the cognitive- code approach to the study of a second language as an alternative to the audio-lingual method dominant at the time. They advocated the conscious study of language rules as central to the learning of a foreign language. CCLT is accepted as a merger of Chomsky's Transformational Grammar and Carroll's Psychology (Carroll, 1965). It is based on Gestalt psychology as well as formational Generative Grammar (Chastain, 1969:98).  "...learning a language is a process of acquiring conscious control of the phonological, grammatical, and lexical patterns of the second language, largely through study and analysis of these patterns as a body of knowledge." (Carroll, 1966:102). A conscious study of language rules as central to the learning of a foreign language. As a theory, it attaches more importance to the learner's understanding of the structure of the foreign language. Rule- deduction is a facility, which develops automatically with use of the language in meaningful situations within meaningful drillings. By emphasizing mental processes, CCLT places itself in opposition to behaviorism, which largely ignores mental processes. Therefore, CCLT is briefly said to have replaced Behaviorism in the late 1960s.  The term "cognitive-code" indicates any conscious attempt to organize foreign language teaching materials around a grammatical syllabus so as to make way for meaningful practice and practical use of language. One of its most important precepts is meaningful practice. Language practice is must be meaningful, then the learner understands the rules involved in practice in relation to the goal of gaining conscious control of the grammatical, lexical, and auditory patterns. Thus, CCLT represents a sharp contrast to the Audio-lingual Method which relies on pattern drills as a means of teaching syntax, with explicit explanation of grammatical rules.